KNOWING THE CHARACTERISTICS BEHAVIOUR OF EARLY CHILDHREN - Zulminiati, Ms (Indonesian Journal of Early Childhood Education Studies, 2012)
In essence, the development ofearly child renbehavior follows thestages through which every individu. Kecepatan development ofÂ  every childis different,so the formation of different characteristics pula. A child can go faster progress compared toapeerfriends, while others in the field is slower.This is whatled to the development of eachchild is unique., but basically there are certain characteristics that characterize their behavior a teach stage. Behavioral characteristics ofearly childhood is the formation of a number of positive behaviors, through aprocess oflearningin education, withchildrento cultivatea warenessof himselfto maturityandthe DAPT kedewasaan. Halobtained through observation, keteladanan dan social interaction. Behavior that develops in early childhood among which is, self-concept, self-centered, empathy, problem solving, physical /movement, thought and language.